A New Silica-Rich Material from Waste Fly Ash – Generation, Characterisation and Study of Its Effectiveness as a Filler for Rubber Compounds. Issue 6 (July 2014) - Dasgupta, Mridul; Gupta, Saikat Das; Mukhopadhyay, Rabindra; Bandyopadhyay, Abhijit
A silica-rich material was generated from waste fly ash and it was subsequently characterized and experimented in ESBR compounds to find its suitability to be used as a filler for rubber compounds. This material contained 97.5% silica and 2.5% alumina. Characterisation of this material, designated as Modified Fly Ash (MFA), revealed the presence of characteristic peaks of silica in an FTIR study, and the surface area was found to be 110–115 m 2 /g. The effect of this material as a filler for rubber compound has been studied in ESBR compounds at low, medium and high filler loadings, and the compound properties were compared with those of compounds filled with two commercially available grades of silica, namely VN2-Silica (surface area 120–125 m 2 /g) and VN3-Silica (165–170 m 2 /g), at similar loadings. MFA showed the highest cure rate index, elongation at break and lowest heat generation among the three fillers at all the levels of filler loading. The tensile strength and 300% modulus of MFA filled compounds were inferior to those of VN3-silica, but they were closer to the values obtained for VN2-silica filled compounds. These two properties of MFA and VN2-Silica were comparable at low filler loading and at medium to high loading, the properties exhibited by VN2-Silica could be matched by using higher dosage of MFA.